2022
DOI: 10.3390/ani12212923
|View full text |Cite
|
Sign up to set email alerts
|

Use of Multivariate Adaptive Regression Splines Algorithm to Predict Body Weight from Body Measurements of Anatolian buffaloes in Türkiye

Abstract: Anatolian buffalo is an important breed reared for meat and milk in various regions of Türkiye. The present study was performed to estimate body weight (BW) from several body measurements, such as tail length (TL), shoulder height (SH), withers height (WH), body length (BL), chest circumference (CC), shank diameter (SD) and birth weight (BiW). The data set was taken from Muş Province of Türkiye. In this respect, 171 Anatolian buffaloes were used. To estimate the BW, different proportions of the training and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Our MARS model performance results implied that MARS might be useful for the prediction of live body weight from linear body measurements in goats using 70:30 dataset proportion for training and test sets. These findings agree with Ağyar et al’s [ 31 ] suggestion that the multivariate adaptive regression splines data mining algorithm had better identification properties than other estimation models.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our MARS model performance results implied that MARS might be useful for the prediction of live body weight from linear body measurements in goats using 70:30 dataset proportion for training and test sets. These findings agree with Ağyar et al’s [ 31 ] suggestion that the multivariate adaptive regression splines data mining algorithm had better identification properties than other estimation models.…”
Section: Discussionsupporting
confidence: 92%
“…Due to the scarcity of MARS data mining algorithm studies in goats, we discussed our MARS findings using different animal species. Ağyar et al [ 31 ] indicated that the MARS results determined tail length, body length, chest circumference and shank diameter as important parameters in Anatolian buffaloes in Turkiye. The MARS results implied that sex, withers height, rump height, body length and heart girth might be useful for the improvement of live body weight in Savanna goats.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, buffalo farming is an important livestock activity in Mexico because it represents a potential source of milk, dairy products, and meat (Hossein-Zadeh, 2016; Mota-Rojas et al ., 2022). The buffalo offers several important advantages over cattle, such as better adaptation to the type of climate, greater resistance to tropical cattle diseases, and better use of low-quality forage (Torres-Chable et al , 2017; Ağyar et al ., 2022). In Mexico, the water buffalo ( Bubalus bubalis ) was introduced in regions with a hot and humid climate, mainly in the states of Veracruz, Tabasco, Chiapas, and Campeche, due to the fact that in these areas there are large wetlands, which are the natural habitat of these animals (Peralta-Torres et al ., 2020).…”
mentioning
confidence: 99%
“…Although buffalo farming is perceived by producers as a profitable business, there is still much to be explored in terms of animal production parameters (Hernández-Herrera et al , 2018). In particular, the growth rate is an important parameter in animal production, as it characterizes the adaptability and economic suitability of livestock production (Ağyar et al ., 2022). Animals that grow faster in terms of body weight must also initiate early physiological functioning of reproduction and milk production (Thiruvenkadan et al ., 2009; Gurgel et al ., 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation